Is Parental Leave Costly for Firms and Coworkers? - Anne Ardila Brenøe; Serena Canaan; Nikolaj Harmon; Heather Royer (Institute of Labor Economics (IZA), 2019)
Most of the existing evidence on the effectiveness of family leave policies comes from studies focusing on their impacts on affected families – that is, mothers, fathers, and their children – without a clear understanding of the costs and effects on firms and coworkers. We use data from Denmark to evaluate the effect on firms and coworkers when a worker gives birth and goes on leave. Using a dynamic difference-in-differences design, we compare small firms in which a female employee is about to give birth to an observationally equivalent sample of small firms with female employees who are not close to giving birth. Identification rests on a parallel trends assumption, which we substantiate through a set of natural validity checks. When an employee gives birth she goes on leave from her firm for 9.5 months on average. Firms respond by increasing their labor inputs along several margins such that the net effect on total work hours is close to zero. Firms' total wage bill increases in response to leave take up, but this is driven entirely by wages paid to workers on leave for which firms receive reimbursement. There are no measurable effects on firm output, profitability or survival. Finally, coworkers of the woman going on leave see temporary increases in their hours, earnings, and likelihood of being employed but experience no significant changes in well-being at work as proxied by sick days. Overall, our results suggest that employees going on parental leave impose negligible costs on their firm and coworkers.
Keywords: H00; J2; J13; 330; family leave; birth; firms; labor